Propuesta de documentación para el sistema de gestión de calidad de la competencia técnica de un laboratorio de control de calidad (2021)
The quality management system in the control laboratories is a determining factor to demonstrate technical competence, guarantee the reliability of analyzes and the validity of their results. This work aims to make a proposal for the creation and updating of documented information in a pharmaceutical quality control laboratory based on the international standard ISO 9001 for quality management systems and ISO / IEC 17025: 2017 on general requirements for the competence of a testing and calibration laboratory. It starts from the diagnosis of the laboratory documentation case study against the fulfillment of the requirements of the applicable international standards. Subsequently, the information update proposal was structured for laboratory accreditation purposes. The results show the importance of keeping ten procedures documented and their respective records, in such a way as to provide evidence of the conformity of the activities carried out in the laboratory processes.